2016
DOI: 10.1175/jcli-d-15-0065.1
|View full text |Cite
|
Sign up to set email alerts
|

The South American Water Balance: The Influence of Low-Level Jets

Abstract: To study the climatology of the water balance over South America and analyze the influence of low-level jets (LLJs), a climate study of the water balance and its main components was performed, specifically in the Amazon and La Plata basin (LPB) region, from 1979 to 2008. The results showed that on average for the analysis period, the Amazon basin and LPB performed as a sink of moisture (ET < P) and as a moisture convergence for the regions, which accounted for approximately 62% and 43% of the precipitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 40 publications
2
26
0
Order By: Relevance
“…During summer, jet events are more influenced by the penetration of the northeasterly trade winds across the Amazon, whereas the South Atlantic subtropical high and the upper level subtropical jet stream are more likely to influence jet events during the fall and winter. These results support the description of large-scale circulation and moisture transport patterns presented in previous studies of the SALLJ (Marengo et al, 2004;Nascimento et al, 2016;Wang & Fu, 2004).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…During summer, jet events are more influenced by the penetration of the northeasterly trade winds across the Amazon, whereas the South Atlantic subtropical high and the upper level subtropical jet stream are more likely to influence jet events during the fall and winter. These results support the description of large-scale circulation and moisture transport patterns presented in previous studies of the SALLJ (Marengo et al, 2004;Nascimento et al, 2016;Wang & Fu, 2004).…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies (Marengo et al, 2002(Marengo et al, , 2004Nascimento et al, 2016) have identified SALLJ events by applying the Bonner criteria to reanalysis data. The Bonner criteria for identifying low-level jet events are as follows: (1) northerly winds (850 hPa) with speeds ≥12 m/s, (2) vertical wind shear between 850 and 700 hPa ≥ 6 m/s, (3) meridional component larger than the zonal component, and (4) meridional winds from the north.…”
Section: 1029/2018jd029634mentioning
confidence: 99%
See 2 more Smart Citations
“…LLJs are relevant components of the global atmospheric system because in several regions they are responsible for transporting heat and water vapor poleward into the extratropics (Stensrud 1996;Marengo et al 2004;Vera et al 2006). In subtropical South America, the north-northwesterly LLJ often observed east of the Andes mountain range, and referred to as the South American low-level jet (SALLJ) (Vera et al 2006), plays a crucial role in the hydrological cycle of the La Plata basin and surrounding areas (Berri and Inzunza 1993;Salio et al 2002, hereafter SNS02;Marengo et al 2004; M. G. Nascimento et al 2016). The SALLJ is a component of the environment that leads to deep convection in the La Plata basin since it sets up a moist, unstable environment and promotes low-level lifting at its exit region or as it impinges on the Andes foothills and Sierras de Córdoba (Salio et al 2007;Rasmussen and Houze 2011;Rasmussen et al 2014;Rasmussen and Houze 2016).…”
Section: Introductionmentioning
confidence: 99%